Piezoelectricity in Amine Functionalized Reduced Graphene Oxide. (2018) - Roy, Dilip; Nandi, Anupam; Bardhan Roy, Arijit; Majumdar, Sanhita; Mandal, Sourav; Kundu, Avra; Minhaz Hossain, Syed
Abstract: Piezoelectric materials have various applications ranging from macro level vibration sensor to nano-electromechanical devices. In this work, we have investigated the piezoelectric property of amine functionalized Reduced Graphene Oxide (af-RGO) deposited on SiO2, thermally grown on micro machined Si cantilever. The synthesized af-RGO was characterized by Raman spectroscopy and field emission scanning electron microscopy. The fabricated device was forced to vibrate for studying its piezoelectric property. The output of the device was fed to an AC multimeter to observe the electromechanical response. The output response shows about 400% increase when forced to mechanical vibration.